The "sex gap" in COVID-19 trials: a scoping review. (December 2020) - Schiffer, Veronique M.M.M.; Janssen, Emma B.N.J.; van Bussel, Bas C.T.; Jorissen, Laura L.M.; Tas, Jeanette; Sels, Jan-Willem E.M.; Bergmans, Dennis C.J.J; Dinh, Trang H.T.; van Kuijk, Sander M.J.; Hana, Anisa; Mehagnoul-Schipper, Jannet; Scheeren, Clarissa I.E.; et al.
Abstract: Background: Many studies investigate the role of pharmacological treatments on disease course in Corona Virus Disease 2019 (COVID-19). Sex disparities in genetics, immunological responses, and hormonal mechanisms may underlie the substantially higher fatality rates reported in male COVID-19 patients. To optimise care for COVID-19 patients, prophylactic and therapeutic studies should include sex-specific design and analyses. Therefore, in this scoping review, we investigated whether studies on pharmacological treatment in COVID-19 were performed based on a priori sex-specific design or post-hoc sex-specific analyses. Methods: We systematically searched PubMed, EMBASE, UpToDate, clinical trial.org, and MedRxiv for studies on pharmacological treatment for COVID-19 until June 6th, 2020. We included case series, randomized controlled trials, and observational studies in humans (≥18 years) investigating antiviral, antimalarial, and immune system modulating drugs. Data were collected on 1) the proportion of included females, 2) whether sex stratification was performed (a priori by design or post-hoc), and 3) whether effect modification by sex was investigated. Findings: 30 studies were eligible for inclusion, investigating remdesivir ( n  = 2), lopinavir/ritonavir ( n  = 5), favipiravir ( n  = 1), umifenovir ( n  = 1), hydroxychloroquine/chloroquine ( n  = 8), convalescent plasma ( n  = 6), interleukin-6 (IL-6) pathway inhibitors ( n  = 5), interleukin-1 (IL-1) pathway inhibitors ( n  = 1) and corticosteroids ( n  = 3). Only one study stratified its data based on sex in a post-hoc analysis, whereas none did a priori by design. None of the studies investigated effect modification by sex. A quarter of the studies included twice as many males as females. Interpretation: Analyses assessing potential interference of sex with (side-)effects of pharmacological therapy for COVID-19 are rarely reported. Considering sex differences in case-fatality rates and genetic, immunological, and hormonal mechanisms, studies should include sex-specific analyses in their design to optimise COVID-19 care. Funding: None